Modeling and analyzing the microwave energy absorption of paddy and mortality assessment of insects - Md. Manjur Ahmed (School of Manufacturing Engineering, 2012)
In this thesis, dielectric modeling of paddy and insect (R. dominica) was developed to analyze the characteristics for microwave heat treatment to the Malaysian paddy MR219.